Innovative Digital Master Book for Efficient and Secure Student Data Management at MTs.N 9 Jember - Nastolib, Irhason; Zahro, Siti Fatimatus; Karsum, Rahmad (IJIE International Journal of Islamic Education, 2024)
Madrasah Tsanawiyah Negeri 9 Jember is a madrasah located in Kencong Village, Jember Regency. The management of student master books in this madrasa has been carried out in accordance with the Standard Operating Procedure (SOP), but its implementation is still manual. Manual recording of student data is prone to writing errors, data loss, and the difficulty of searching or updating information. Therefore, a digital-based master book innovation was carried out. The purpose of this study is to identify how the application of digital master books can improve efficiency and security in student data management. This study is a qualitative study with a case study type: Data collection techniques were obtained through observation, interviews, and documentation methods. The results of the study showed that the innovation of digital master books succeeded in significantly increasing the efficiency of data management, especially in terms of the speed of access and archiving of student data. Data security is also more guaranteed through the use of layered protection systems such as encryption and limited access control that can minimize the risk of data leakage.